NGHIÊN CỨU CHẾ TẠO KEO 88CA.VN DÙNG THAY THẾ KEO 88CA NHẬP NGOẠI - Bùi, Thị Hồng Phương; Phạm, Duy Nam; Vương, Văn Trường (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDYING ON MANUFACTURING 88CA.VN ADHESIVE FOR REPLACING THE IMPORTED 88CA ADHESIVE 88CA adhesive is a glue, made from neoprene rubber, p-t-butylphenol formaldehyde resin and solvent. Using 88CA adhesive, the rubber could be linked to metal, glass, leather, wood, concrete and other surfaces by cold paste method. 88CA glue is widely applied for various purposed in production of automobile, aircraft, softwood and can be applied for various purposes. 88CA.VN glue is completely manufactured with available materials in Vietnamese market to meet the technical specifications TY 38.105.1760-89. 88CA.VN adhesive completely replace imported 88CA glue.